Ultrasound scanning in the diagnosis of peripheral neuropathies. Issue 3 (4th February 2021) - Telleman, Johan A; Herraets, Ingrid JT; Goedee, H Stephan; van Asseldonk, J Thies; Visser, Leo H
Abstract : Nerve ultrasound scanning has become a valuable diagnostic tool in the routine workup of peripheral nerve disorders, effectively complementing conventional electrodiagnostic studies. The most relevant sonographic features are nerve size and structural integrity. Several peripheral neuropathies show characteristic and distinct patterns of nerve enlargement, allowing their early and accurate identification, and reducing test-burden and diagnostic delay for patients. In mononeuropathies such as carpal tunnel syndrome and ulnar neuropathy at the elbow, nerve enlargement develops only at specific sites of entrapment, while in polyneuropathy the nerve enlargement may be multifocal, regional or even diffuse. Nerve ultrasound scanning can reliably identify chronic inflammatory neuropathies, even when extensive electrodiagnostic studies fail, and it should therefore be embedded in routine diagnostic workup of peripheral neuropathies. In this paper we describe a potential diagnostic strategy to achieve this.